Kualitas Pertemanan di Kalangan Siswa Berbakat: Menelusuri Peran Overexcitability - Kosasih, Ismawati; Chotidjah, Sitti; Zulnida, Eka Fauziyya (Nusantara: Jurnal Pendidikan Indonesia, 2025)
Purpose – Various empirical findings suggest that gifted students possess distinct traits, including heightened overexcitability. Overexcitability is associated with both positive potential and psychological conflicts, one of which is poor social relationship quality. However, only a few studies have confirmed the relationship between overexcitability and poor social relationships. This study was conducted to examine whether overexcitability affects the quality of friendship.Method – The study employed a quantitative approach with a correlational design. A total of 111 elementary, middle, and high school students participated, consisting of 23 identified gifted students, 38 students with superior intelligence, and 50 students with average intelligence. Overexcitability was measured using the Overexcitability Questionnaire II (OEQ-II), while friendship quality was measured using the Friendship Network Satisfaction Scale. The data obtained was analyzed using simple and multiple linear regression techniques, and one-way ANOVA. Findings – The results showed a significant effect of overexcitability on friendship quality (R Square = .210, sig. < .001). The difference test results revealed a significant difference (sig. = .005) in friendship quality among the gifted (m = 58.217), superior (m = 69.631), and average (67.180) intelligence groups. Gifted students were found to have lower friendship quality compared to the other groups (sig. = 0.05). Research Implications – These findings indicate the need for the implementation of psychoeducational programs to improve social skills for gifted students. Gifted students who have intellectual and imaginational overexcitability need to receive more guidance in improving their social interaction skills.